The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ijms20123016
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Hepatogenic Differentiation of Human Wharton’s Jelly–Derived Mesenchymal Stem Cells by Using Three-Step Protocol

Abstract: Currently, human Wharton’s jelly-derived mesenchymal stem cells (hWJ-MSCs) are an attractive source of stem cells for cell-based therapy, owing to their ability to undergo self-renewal and differentiate into all mesodermal, some neuroectodermal, and endodermal progenies, including hepatocytes. Herein, this study aimed to investigate the effects of sodium butyrate (NaBu), an epigenetic regulator that directly inhibits histone deacetylase, on hepatic endodermal lineage differentiation of hWJ-MSCs. NaBu, at 1 mM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…When cells were treated with small molecules individually, stable or upregulated cell viability was observed. Many papers report tendencies that agree with our results with decitabine ( Pang et al, 2019 ), TSA ( Han et al, 2013 ), NaBut ( Panta et al, 2019 ), RA ( Pourjafar et al, 2017 ), vitC ( Markmee et al, 2019 ). Decitabine is a well-known hypomethylating agent which incorporates itself into host DNA, but is used as a drug to treat myelodisplastic syndrome and acute myeloid leukemia.…”
Section: Discussionsupporting
confidence: 91%
“…When cells were treated with small molecules individually, stable or upregulated cell viability was observed. Many papers report tendencies that agree with our results with decitabine ( Pang et al, 2019 ), TSA ( Han et al, 2013 ), NaBut ( Panta et al, 2019 ), RA ( Pourjafar et al, 2017 ), vitC ( Markmee et al, 2019 ). Decitabine is a well-known hypomethylating agent which incorporates itself into host DNA, but is used as a drug to treat myelodisplastic syndrome and acute myeloid leukemia.…”
Section: Discussionsupporting
confidence: 91%
“…However, the translation of these studies to UC-MSC is still limited. To the best of our knowledge, only Panta et al [26] showed that pre-treatment of UCM-MSCs with NaBu upregulated hepatoblast and hepatocyte markers and stimulated mature hepatic-associated functions, such as urea production, glycogen storage and G6P, CEBPA, and CYP2B6 activity, compared to non-treated differentiated cells.…”
Section: Histone Modificationsmentioning
confidence: 96%
“…Stepwise addition of factors such as EGF, FGF, HGF, nicotinamide, ITS, dexamethasone or OSM to the culture medium is used in the majority of the studies to differentiate MSCs [23,26,34,35,41]. Although the addition of these factors seems to lead to hepatic differentiation, a full mature hepatic cell has not yet been achieved.…”
Section: Epigenetic Modifiers For Improving Hlc Phenotypementioning
confidence: 99%
“…The use of CHIR99021 reduce concentrations of activin A without affecting the differentiation rate of endoderm (Farzaneh et al, 2018). Sodium butyrate and valproic acid are histone deacetylation inhibitors that can promote the differentiation of definitive entoderm into liver-specific cells (Kondo et al, 2014;Panta et al, 2019). Trichostatin A, 5-aza, and nanomycin A, all of which are epigenetic modifiers, can be employed to induce differentiation of HLCs (Seeliger et al, 2013;Cipriano et al, 2017;Nakamae et al, 2018).…”
Section: Chemical Approach Adding Exogenous Substancesmentioning
confidence: 99%